CDCA5 promoted cell invasion and migration by activating TGF-β1 pathway in human ovarian cancer cells - Qingsong Zhang; Rong Zhang; Yuzhi Li; Xiaojun Yang (Journal of Ovarian Research, 2024)
Abstract Background The gene cell division cycle associated 5 (CDCA5), also called sororin, has oncogenic characteristics and is upregulated in various carcinomas. Nevertheless, the involvement of CDCA5 in ovarian cancer (OC), a highly aggressive form of cancer, and the underlying mechanism of metastasis remain inadequately investigated. Results The bioinformatics data revealed a negative correlation between the patient’s survival and CDCA5 expression, which was overexpressed in OC. Functional assays also confirmed high expression levels of CDCA5 in OC tissues and cells. This suggests that CDCA5 may potentially enhance the motility, migration, and proliferation of OC cells invitro. It impedes DNA damage and apoptosis in OC cells, inhibiting xenograft development in nude mice. The RNA sequencing results suggest CDCA5 is majorly associated with biological functions related to the extracellular matrix (ECM) and influences the transforming growth factor (TGF) signaling pathway. Moreover, subsequent functional investigations elucidated that CDCA5 facilitated the migration and invasion of OC cells viathe TGF-β1/Smad2/3 signaling pathway activation. Conclusions CDCA5 may be a strong potential therapeutic target for the treatment and management of OC.